Martensite-austenite transition correlated twinning and symmetry breaking in single crystalline Ni50Mn35In15 - Chen, Y. S.; Lin, J. G.; Singh, S.; Manna, Kaustav; Fecher, Gerhard H.; Felser, Claudia (Physical Review Materials, 2021)
Temperature-dependent ferromagnetic resonance (FMR) spectroscopy was used to investigate a Ni50Mn35In15 single crystalline slab to understand the nature of its martensitic transition. Its magnetic anisotropy in multivariant martensitic structures depends on external stress and strain. Near the transition, the preferred orientation of a pair of twinned domains with easy axes along [100]A and [010]A is observed in Ni50Mn35In15. The temperature dependence of the g value indicates a unique characteristic with an opposite shift of g away from 2 in the austenite and martensite phases. This indicates a transition from quenched to unquenched states of electron orbital motion that is induced by breaking the inversion symmetry during the phase transition. The FMR result is magnetic evidence for the martensitic transition and thus it advances our scientific understanding on this unique structural transformation.
CRIS-Team Scopus Importer:2022-04-14